SECURITY SIMULATION OF SEA TOLL TRACK BY KRI HEADQUARTER ELEMENTS CORRESPONDING SECTOR OF MARITIME SECURITY OPERATIONS EAST REGION - Agus Tri Haryanto; Sri Gunani Pratiwi; Bambang Ispri (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
The concept of Sea Toll which is a Pivot of World Maritime policy programs contributes to National equalization. Where the role of the pioneer ship in the region, especially East Java Province into one of the security programs. Related to maritime security, Lantamal V has the power KRI element to support security operations these pioneer ship lines. By using the Simulation method, model the security designed according to the behavior of an operating system of KRI and sea transport of pioneer ship, so that gives the picture and pattern operate for in the execution of decision making for strategic to head TNI AL in the plan operate for Keyword: Pivot Maritime, Concept of Sea Toll, Simulation.